The Roots of Reform: Islamic Education and the Early Modernization Process in 18th Century Egypt - Asril Umar; Boyke Azwar; Ade Lestari (Bulletin of Indonesian Islamic Studies, 2025)
This research explores the transformation of Islamic education in 18th-century Egypt, focusing on reform strategies, modernization aspects, key figures, and their impacts. Using a qualitative approach through documentation studies and in-depth interviews, data were collected from written sources, biographies, and intellectual works. Thematic analysis was applied to identify central ideas and their influence on educational development. Interviews with Islamic history experts, academics, or researchers who are competent in this field can provide further insights into the interpretation and a deeper understanding of the contributions of these figures to education. The findings reveal that Islamic education in Egypt experienced major reforms, especially through the integration of modern and secular sciences alongside traditional religious studies. Pioneering figures such as Muhammad Ali Pasha, Rifa’a al-Tahtawi, and Muhammad Abduh were instrumental in reshaping educational institutions, curricula, and teaching methods. These reforms laid the foundation for modern education in Egypt and influenced broader Islamic educational practices. The study recommends the continued integration of religious and secular knowledge to build a holistic and contextually relevant education system.